Management of infection prevention and control in the development of new hospital buildings – effective stakeholder engagement during design and construction. Issue 3 (1st November 2022) - Roche, F; Hare, B; Curtis, K; Price, L
Abstract: Specific elements of building services such as heating, ventilation or water supply systems can play a key role in infection prevention and control (IPC) within hospital buildings and links between the design of such systems and increased rates of healthcare associated infections (HAI) have been identified. These links are complex and multifactorial and several issues have a bearing on this relationship during the construction of a hospital buildings. One such issue is the nature and efficacy of the engagement of IPC specialists employed by the client end user during the development process. Good management of IPC issues not only supports effective IPC team engagement but depends upon it to achieve key aims. Research suggests, however, that the quality of IPC team engagement is not always optimal and there is a gap in knowledge around how this can be addressed. This research focuses on a qualitative evaluation of the nature and efficacy of the engagement of IPC teams in the construction lifecycle development of new hospitals. Using in-depth interview data, the experiences of IPC team members will be explored and barriers and facilitators to high quality engagement identified. This data will be used to develop the foundational principles of an improvement strategy for the engagement of IPC teams within the construction lifecycle development of new hospitals in the UK. Post-pandemic, the role of the built environment in the spread of infection and the processes developed to manage this will be under increased scrutiny. This paper adds to this growing body of research.